Flatness and structural analysis as a constructive framework for private communication. (November 2018) - Dravie, B.; Guillot, P.; Millérioux, G.
Abstract: This paper deals with the use of control theoretical concepts, essentially flatness, along with structural analysis, in the context of private communication. A new and systematic methodology to design a cryptographic architecture belonging to the special class of ciphers called Self Synchronizing Stream Ciphers (SSSC) is proposed. Till now, the constructions of SSSC were based on automata with finite input memory involving shifts or triangular functions ( T -functions) as state transition functions. Besides, only ad-hoc approaches were available in the literature. The contribution of this paper is to propose a general framework to design SSSC involving dynamical systems taking the form of switched linear systems over finite fields with arbitrary state transition functions. An example of cipher with complete specifications is given. Its implementation on a small scale breeding of an ICS-SCADA equipment is described.